Association between examined lymph node count and survival in resectable cervical cancer: a retrospective analysis using SEER data - Jing Gao; Jing Gao; Wanchun Yin; Zhiqing Zhang; Qin Zhou (Frontiers in Oncology)
BackgroundThe optimal examined lymph node (ELN) in resectable nonmetastatic cervical cancer patients remains controversial.MethodsA total of 7435 N0 patients and 1385 N1 patients were enrolled from the Surveillance, Epidemiology, and End Results database. The relationship between ELN and cancer-specific surcical (CSS) was evaluated by restrictive cubic spline (RCS) method. Survival analysis was performed by using Kaplan–Meier method.ResultsThe median ELN count decreased over years both in N0 and N1 patients. The RCS illustrated nonlinear relationships between ELN counts and prognosis for N0 patients (nonlinearity, p= 0.026; optimal ELN: 13) and N1 patients (nonlinearity, p= 0.024; optimal ELN: 14). Patients were divided into ELN adequate and limited groups according to the optimal cutoff of ELN. The 5-yr and 10-yr survival rates were 94.4% and 92.5% for N0 adequate patients, and 93.9% and 90.0% for N0 limited patients. The 5-yr and 10-yr survival rates were 73.8% and 70.3% for N1 adequate patients, and 68.6% and 63.5% for N1 limited patients. For N0 patients, no survival benefit was found in additional adjuvant treatment. For N1 adequate patients, those with adjuvant radiotherapy obtained greatest survival benefit. For N1 limited patients, those with adjuvant radiotherapy or radiotherapy plus chemotherapy obtained better survival.ConclusionsNonmetastatic cervical cancer patients with clinical N0 and N1 stages who had at least 13 and 14 ELN counts, respectively, showed better long-term survival. Further prospective studies are needed to validate the association between ELN count and long-term survival.